Circularly Permuted Far-Red Fluorescent Proteins - Tianchen Wu (MDPI AG, 2021)
The color palette of genetically encoded fluorescent protein indicators (GEFPIs) has expanded rapidly in recent years. GEFPIs with excitation and emission within the “optical window” above 600 nm are expected to be superior in many aspects, such as enhanced tissue penetration, reduced autofluorescence and scattering, and lower phototoxicity. Circular permutation of fluorescent proteins (FPs) is often the first step in the process of developing single-FP-based GEFPIs. This study explored the tolerance of two far-red FPs, mMaroon1 and mCarmine, towards circular permutation. Several initial constructs were built according to previously reported circularly permuted topologies for other FP analogs. Mutagenesis was then performed on these constructs and screened for fluorescent variants. As a result, five circularly permuted far-red FPs (cpFrFPs) with excitation and emission maxima longer than 600 nm were identified. Some displayed appreciable brightness and efficient chromophore maturation. These cpFrFPs variants could be intriguing starting points to further engineer far-red GEFPIs for in vivo tissue imaging.